2017
DOI: 10.1002/2016tc004407
|View full text |Cite
|
Sign up to set email alerts
|

Th‐Pb ion probe dating of zoned hydrothermal monazite and its implications for repeated shear zone activity: An example from the Central Alps, Switzerland

Abstract: Th‐Pb age dating of zoned hydrothermal monazite from alpine‐type fissures/clefts is a powerful tool for constraining polyphase deformation at temperatures below 350°C and presents an alternative to K/Ar and 40Ar/39Ar dating techniques for dating brittle tectonics. This study considers the relationship between cleft orientations in ductile shear zones and cleft mineral crystallization during subsequent brittle overprinting. In the Grimsel area, located in the Aar Massif of the Central Alps, horizontal clefts fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 52 publications
2
52
0
Order By: Relevance
“…Th diffusion is approximately 3 times slower than Pb diffusion (Cherniak & Pyle, 2008), and therefore, the Th-U-Pb system should remain closed in monazite under low-grade metamorphic conditions. Nevertheless, monazite commonly records low-grade metamorphic and hydrothermal events (e.g., Bergemann et al, 2017;Just et al, 2010;Oyhantçabal et al, 2012;Poitrasson et al, 1996;Teufel & Heinrich, 1997). Such disturbances of the Th-U-Pb system seem to arise from mechanisms, such as neocrystallization, recrystallization, and dissolution/reprecipitation, instead from diffusive exchange (Cherniak et al, 2004;Cherniak & Pyle, 2008;Gardés et al, 2006;Harlov et al, 2011;Kelsey et al, 2008;Oriolo et al, 2018).…”
Section: The Basement Record Of Mesozoic Tectonomagmatic Eventsmentioning
confidence: 99%
“…Th diffusion is approximately 3 times slower than Pb diffusion (Cherniak & Pyle, 2008), and therefore, the Th-U-Pb system should remain closed in monazite under low-grade metamorphic conditions. Nevertheless, monazite commonly records low-grade metamorphic and hydrothermal events (e.g., Bergemann et al, 2017;Just et al, 2010;Oyhantçabal et al, 2012;Poitrasson et al, 1996;Teufel & Heinrich, 1997). Such disturbances of the Th-U-Pb system seem to arise from mechanisms, such as neocrystallization, recrystallization, and dissolution/reprecipitation, instead from diffusive exchange (Cherniak et al, 2004;Cherniak & Pyle, 2008;Gardés et al, 2006;Harlov et al, 2011;Kelsey et al, 2008;Oriolo et al, 2018).…”
Section: The Basement Record Of Mesozoic Tectonomagmatic Eventsmentioning
confidence: 99%
“…In situ SIMS or LA‐ICP‐MS dating of zoned hydrothermal cleft or fissure‐vein monazite‐(Ce) (hereafter simply monazite) offers the possibility to constrain the history of low‐grade metamorphic areas that experienced multiple phases of ductile to brittle deformation (e.g., Bergemann et al., ; Grand'Homme et al., ). The understanding of these areas is classically hampered by a variety of problems encountered when employing (thermo) chronological approaches based on Rb–Sr, K–Ar, Ar–Ar, fission‐track and U–Th/He techniques to polymetamorphic rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Fissure‐vein monazite grows in fluid‐filled pockets with fluid‐enhanced reaction kinetics at temperatures at or below ~350°C (Bergemann et al., ; Gnos et al., ; Grand'Homme, ). It has been shown that strong tectonic movement disturbs the chemical equilibrium in the fluid‐filled pocket without deforming the crystals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations